Cardiopathology in Methamphetamine Poisoning-Related Deaths in Chiang Mai Thailand (Indian Journal of Forensic Medicine & Toxicology, 2024)
Background: Blood Methamphetamine levels have been utilized to assess methamphetamine exposure and its toxicity. Heart is a major target organ of methamphetamine intoxication. In some autopsy cases heart pathologies have been revealed at low level of methamphetamine and extensively to be understand a relationship between the blood methamphetamine level and heart pathology.Aim: The aim of this study was to assess the relationship between blood methamphetamine level and heart pathology by using postmortem cases.Methodology: One hundred and twenty medico-legal cases were included and blood methamphetamine or amphetamine levels in whole blood along with heart pathological finding were determined.Results: Coronary atherosclerosis, myocardial fiber hypertrophy, and fibrosis of the left ventricular myocardium were highly frequency findings in methamphetamine intoxication. Interestingly, forensic cases revealed myocardial fiber hypertrophy in chronic methamphetamine users.Conclusion: The levels of methamphetamine and amphetamine associated with myocarditis, cardiomyopathy and dystrophic calcification mitral valve. Evaluation of methamphetamine and amphetamine levels are key biomarkers for predicting the seriousness of heart-related pathological conditions.
Keywords: Methamphetamine, Amphetamine, heart pathology, Arteriosclerosis, Blood Methamphetamine level.